Composition and interrelationships of a large Neotropical freshwater fish group, the subfamily Cheirodontinae (Characiformes: Characidae): A case study based on mitochondrial and nuclear DNA sequences - Mariguela, T. C. [UNESP]; Ortí, G.; Avelino, G. S. [UNESP]; Abe, K. T. [UNESP]; Oliveira, C. [UNESP] (Elsevier, 2013)
•Relationships of Cheirodontinae based on a broad taxonomic sample.•Results reject the monophyly of Cheirodontinae as previously conceived.•Exclusion of Amazonspinther and Spintherobolus from the subfamily Cheirodontinae.•The removal of Leptagoniates pi of the genus Leptagoniates and inclusion in Cheirodontinae.•Division of Cheirodontinae in three newly defined monophyletic tribes. Characidae is the most species-rich family of freshwater fishes in the order Characiformes, with more than 1000 valid species that correspond to approximately 55% of the order. Few hypotheses about the composition and internal relationships within this family are available and most fail to reach an agreement. Among Characidae, Cheirodontinae is an emblematic group that includes 18 genera (1 fossil) and approximately 60 described species distributed throughout the Neotropical region. The taxonomic and systematic history of Cheirodontinae is complex, and only two hypotheses about the internal relationships in this subfamily have been reported to date. In the present study, we test the composition and relationships of fishes assigned to Cheirodontinae based on a broad taxonomic sample that also includes some characid incertae sedis taxa that were previously considered to be part of Cheirodontinae. We present phylogenetic analyses of a large molecular dataset of mitochondrial and nuclear DNA sequences. Our results reject the monophyly of Cheirodontinae as previously conceived, as well as the tribes Cheirodontini and Compsurini, and the genera Cheirodon, Compsura, Leptagoniates, Macropsobrycon, Odontostilbe, and Serrapinnus. On the basis of these results we propose: (1) the exclusion of Amazonspinther and Spintherobolus from the subfamily Cheirodontinae since they are the sister-group of all remaining Characidae; (2) the removal of Macropsobrycon xinguensis of the genus Macropsobrycon; (3) the removal of Leptagoniates pi of the genus Leptagoniates; (4) the inclusion of Leptagoniates pi in the subfamily Cheirodontinae; (5) the removal of Cheirodon stenodon of the genus Cheirodon and its inclusion in the subfamily Cheirodontinae under a new genus name; (6) the need to revise the polyphyletic genera Compsura, Odontostilbe, and Serrapinnus; and (7) the division of Cheirodontinae in three newly defined monophyletic tribes: Cheirodontini, Compsurini, and Pseudocheirodontini. Our results suggest that our knowledge about the largest Neotropical fish family, Characidae, still is incipient. © 2013 Elsevier Inc..
Keywords: Characids; Freshwater fishes; Molecular phylogeny; Neotropical fishes; Characidae; Characiformes; Cheirodon; Cheirodontinae; Macropsobrycon; Pisces; Stenodon